Mutations targeting the plug‐domain of the Shewanella oneidensis proton‐driven stator allow swimming at increased viscosity and under anaerobic conditions. Issue 5 (21st October 2016) - Brenzinger, Susanne; Dewenter, Lena; Delalez, Nicolas J.; Leicht, Oliver; Berndt, Volker; Paulick, Anja; Berry, Richard M.; Thanbichler, Martin; Armitage, Judith P.; Maier, Berenike; Thormann, Kai M.
Summary: Shewanella oneidensis MR‐1 possesses two different stator units to drive flagellar rotation, the Na + ‐dependent PomAB stator and the H + ‐driven MotAB stator, the latter possibly acquired by lateral gene transfer. Although either stator can independently drive swimming through liquid, MotAB‐driven motors cannot support efficient motility in structured environments or swimming under anaerobic conditions. Using ΔpomAB cells we isolated spontaneous mutants able to move through soft agar. We show that a mutation that alters the structure of the plug domain in MotB affects motor functions and allows cells to swim through media of increased viscosity and under anaerobic conditions. The number and exchange rates of the mutant stator around the rotor were not significantly different from wild‐type stators, suggesting that the number of stators engaged is not the cause of increased swimming efficiency. The swimming speeds of planktonic mutant MotAB‐driven cells was reduced, and overexpression of some of these stators caused reduced growth rates, implying that mutant stators not engaged with the rotor allow some proton leakage. The results suggest that the mutations in the MotB plug domain alter the proton interactions with the stator ion channel in a way that both increases torque output and allows swimming at decreased pmf values. Abstract : The stators of the flagellar motor are key elements with respect to motor function and properties. Here, we report that mutations affecting the so‐called plug domain in MotB allow generation of higher torque and swimming under anaerobic conditions. We hypothesize that this region might be important in the functional adaptation of flagellar motors in bacteria living in different environments.